Chapter Application of the guidelines of the Agency for Digital Italy guidelines and CSA Star self-assessment: A Docustar case study - Calabrese, Pierluigi (Proceedings e report, 2023)
The paper shows the new particularly rigorous regulatory context introduced by the entry into force of the AGID guidelines with reference to the application of the Italian digital administration code on the formation, management and storage of electronic documents. In this regard, a concrete case study of the innovative software Docustar is presented, developed by the innovative SME Stella All in One, an ISO 27001:2013 certified company. The cloud software implemented in this way represents a real revolution both in terms of digital rights management of documents, but also in terms of AGID compliance. In addition, being a cloud software intended for use by the public administration, the system perfectly meets the requirements of the CSA Star Self-Assessment, another focal point together with the ISO 27001 standard to ensure the security of information on application systems.